Business model development for indonesian restaurant daapuandee - Amelya Putri, Zora; Hamsal, Mohamad (The Indonesian Journal of Business Administration, 2018)
Abstract -– Food and beverage industry has a big opportunity in Indonesia. Established on July 2017, Daapuandee is trying this opportunity in this industry providing Padangnese food and another Indonesian foods. This restaurant is a new restaurant, therefore Daapuandee need a proper strategy to develop the business. To help Daapuandee growing in the market, the researcher need analyze the external and internal factors.  The both of data were formed by observation and questionnaire. The researcher conduct the strategy by using TOWS matrix, Porter Generic Strategy dan Strategiy Diamond Model. The result of the business strategy is differentiation strategy such as create innovative product, marketing and promotion activities. On Porter Generic Strategy, the researcher proposed the areas to open new branch, the price, the segment, marketing and promotion using social media. Join on Go-food Grab-food is one of strategy to expand the market and lower the production cost and will impact to increase the sales. Key words: Padangnese Food, Indonesian food, Restaurant, Business Model Development, SWOT